Explaining the intent to start a business among Saudi Arabian University Students - BEN ALI, Tarek (International Review of Management and Marketing, 2016)
Studying entrepreneurial intention has long been an important topic in the field of entrepreneurship. In this paper, we investigate the entrepreneurial intentions of final-year management university students in the Kingdom of Saudi Arabia by applying the theory of planned behavior (TPB). The objectives of the study were to test whether the TPB can help explain the entrepreneurial intentions of university students; to determine whether students will have intentions to start a business and to test the validity of the entrepreneurial intention questionnaire in a Saudi Arabia context. The study was conducted by means of a survey. We found that attitude towards becoming an entrepreneur; perceived behavioural control and subjective norms are positively associated with entrepreneurial intention. Consistent with earlier research, the findings reveal that the TPB is a valuable tool in understanding entrepreneurial intention of Saudi university youth. Most of the students indicated that they intended to start businesses as soon as they had completed their studies and the entrepreneurial intention questionnaire was found to be a valid instrument to measure the entrepreneurial intention in this country. Furthermore, our findings reveal that the moderating effect of some additional contextual determinants does not seem to have a particular effect on predicting entrepreneurial intentions when moderating TPB dimensions. Recommendations for policy makers, entrepreneurship educators and researchers have been suggested.